Altmetrics : a practical guide for librarians, researchers and academics - Tattersall, Andy (Facet Publishing, 2016)
This book gives an overview of altmetrics, its tools and how to implement them successfully to boost and measure research outputs. New methods of scholarly communication and dissemination of information are having a huge impact on how academics and researchers build profiles and share research. This groundbreaking and highly practical guide looks at the role that library and information professionals can play in facilitating these new ways of working and demonstrating impact and influence. Altmetrics focuses on research artefact level metrics that are not exclusive to traditional journal papers but also extend to book chapters, posters and data sets, among other items. This book explains the theory behind altmetrics, including how it came about, why it can help academics and where it sits amongst current measurements of impact. Editor Andy Tattersall draws on the expertise of leading altmetric innovators and practitioners, with chapters from Euan Adie, the founder of Altmetric.com; William Gunn, the Head of Academic Outreach at Mendeley and Ben Showers, author of the bestselling Facet title Library Analytics and Metrics. Readership: Altmetrics will empower library and information professionals working in higher education, researchers, academics and higher education leaders and strategists to develop the skills and knowledge needed to introduce and support altmetrics within their own institutions.--Publisher website.